Love your parents: quran stories for little hearts - Khan, Saniyasnain (GoodwordKidz New Delhi, 2004)
This story emphasizes the importance of honoring and cherishing one's parents, showcasing the deep bond and sacrifices they make for their children. It teaches young readers about gratitude, respect, and the rewards of showing love and kindness to their parents throughout their lives.